2018
DOI: 10.1016/j.yjmcc.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CaMKII activation promotes rapid translocation to its extra-dyadic targets

Abstract: Calcium-calmodulin dependent protein kinase IIδ (CaMKIIδ) is an important regulator of cardiac electrophysiology, calcium (Ca) balance, contraction, transcription, arrhythmias and progression to heart failure. CaMKII is readily activated at mouths of dyadic cleft Ca channels, but because of its low Ca-calmodulin affinity and presumed immobility it is less clear how CaMKII gets activated near other known, extra-dyad targets. CaMKII is typically considered to be anchored in cardiomyocytes, but while untested, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 55 publications
2
33
1
Order By: Relevance
“…To test how the relative dominance of the opposing effects of agonist-induced PKA activity (nuclear retention) or CaMKII activity (nuclear depletion), we first overexpressed CaMKIIδC in cardiomyocytes and treated them with PKA and CaMKII agonists. Under the same experimental conditions we previously found exogenous CaMKIIδ to be 63.2 ± 33% of endogenous CaMKII [ 68 ], which is comparable to the increase seen in heart failure [ 41 ]. The overexpression of CaMKIIδC (as occurs in HF) by itself led to significant nuclear export of HDAC4 (F Nuc /F Cyto decreased from 1 ± 0.02, n = 84 to 0.83 ± 0.02, n = 70; Fig.…”
Section: Resultssupporting
confidence: 71%
“…To test how the relative dominance of the opposing effects of agonist-induced PKA activity (nuclear retention) or CaMKII activity (nuclear depletion), we first overexpressed CaMKIIδC in cardiomyocytes and treated them with PKA and CaMKII agonists. Under the same experimental conditions we previously found exogenous CaMKIIδ to be 63.2 ± 33% of endogenous CaMKII [ 68 ], which is comparable to the increase seen in heart failure [ 41 ]. The overexpression of CaMKIIδC (as occurs in HF) by itself led to significant nuclear export of HDAC4 (F Nuc /F Cyto decreased from 1 ± 0.02, n = 84 to 0.83 ± 0.02, n = 70; Fig.…”
Section: Resultssupporting
confidence: 71%
“…Therefore, the physiological significance of these residues in CAPN1 function warrants further investigation. CaMKII possesses several properties, such as mobility 43 , and serves as a carrier or structural component for substrate transmission 26,27 . Our data showed that self-phosphorylated CaMKII translocated to membrane upon ischemia/ reperfusion challenge, and that CaMKII T287A mutation did not increase the level of CaMKII in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…January (University of Wisconsin–Madison, Madison, WI) and maintained in minimum essential medium supplemented with 10% FBS and 400 µg/ml G418 (Axenia Biologix) as previously described (Zhou et al, 1998). Ventricular myocytes were enzymatically isolated from the rabbit ventricles on the day of electrophysiological experiments as previously described (Wood et al, 2018). HEK cells or cardiac myocytes used for electrophysiological study were adhered to the poly- l -lysine–coated (MW 30,000–70,000; Sigma-Aldrich; 0.1 mg/ml for 2 h at 37°C) coverslips in 12-well plates and transferred to a small recording chamber mounted on the stage of an inverted microscope (Axiovert S100; Carl Zeiss) and were continuously superfused with HEPES-buffered Tyrode’s solution containing (in mM) 137 NaCl, 4 KCl, 1.8 CaCl 2 , 1 MgCl 2 , 10 glucose, and 10 HEPES, pH 7.4 with NaOH.…”
Section: Methodsmentioning
confidence: 99%